Mexico : Human Capital Effects on Wages and Productivity - López-Acevedo, Gladys (World Bank, Washington, DC, 2012)
The authors follow the Hellerstein, Neumark, and Troske (1999) framework to estimate marginal productivity differentials and compare them with estimated relative wages. The analysis provides evidence on productivity and nonproductivity-based determinations of wages. Special emphasis is given to the effects of human capital variables, such as education, experience, and training on wages and productivity differentials. Higher education yields higher productivity. However, highly educated workers earn less than their productivity differentials would predict. On average, highly educated workers are unable to fully appropriate their productivity gains of education through wages. On the other hand, workers with more experience are more productive in the same proportion that they earn more in medium and large firms, meaning they are fully compensated for their higher productivity. Finally, workers in micro and small firms are paid more than what their productivity would merit. Training benefits firms and employees since it significantly increases workers' productivity and their earnings.